Enterotoxin genes, enterotoxin production, and methicillin resistance in Staphylococcus aureus isolated from milk and dairy products in Central Italy. (March 2015) - Carfora, V.; Caprioli, A.; Marri, N.; Sagrafoli, D.; Boselli, C.; Giacinti, G.; Giangolini, G.; Sorbara, L.; Dottarelli, S.; Battisti, A.; Amatiste, S.
Abstract: A total of 227 Staphylococcus aureus colonies, isolated from 54 samples of raw milk and dairy products of bovine, ovine, caprine and bubaline origin were tested for the presence of genes coding for staphylococcal enterotoxins (SEs/SE ls ) and for methicillin resistance. Ninety-three colonies, from 31 of the 54 samples (57.4%) and from 18 (69.2%) of the 26 farms of origin tested positive for SEs/SE ls genes. Most isolates harboured more than one toxin gene and 15 different toxinotypes were recorded. The most frequent were " sec " gene alone (28.6%), " sea, sed, ser, selj " (20%), " seg, sei " and " seh " (8.6%). The 77 colonies harbouring "classical enterotoxins" genes ( sea - sed ) were further tested for enterotoxin production, which was assessed for 59.2% of the colonies. Three methicillin-resistant S. aureus (MRSA) isolates were detected in three different ovine milk/dairy product samples (1.3%). All isolates belonged to spa type t127, sequence type 1, clonal complex 1, SCC mec type IVa.